1996
DOI: 10.1016/0378-1097(96)84201-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipid analysis of Methanopyrus kandleri

Abstract: Non-polar and polar lipids were isolated from Methano~yrus kandleri. Non-polar lipids accounted for 50% w/w of total lipids, with a high proportion of 2,3-di-0-geranylgeranyl-sn-glycerol, 2,3-di-0-phytanyl-sn-glycerol and geranylgeraniol. The core lipids prepared by mild acid methanolysis consisted exclusively of 2,3-di-0-phytanyl-sn-glycerol.Two-dimensional TLC showed mostly glycolipids, and minor amounts of aminophospholipids, phosphoglycolipids and phospholipids. The purification yielded three diglycosyl-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
0
17
2
Order By: Relevance
“…Moreover, in MPK, apart from archaeol derived phytane caldarchaeol derived C 40 , isoprenoids with 0, 1 and 2 cyclopentane rings were found. This, as well as the potential existence of hydroxarchaeaol derived side chains, is in contrast to the ¢ndings of Hafenbradl et al [17] who found only archaeol derived phytane in the polar lipid fraction of MPK. The di¡erent protocols used for total lipid extraction might serve as an explanation for the observed discrepancies.…”
Section: Plel In Archaeacontrasting
confidence: 55%
See 1 more Smart Citation
“…Moreover, in MPK, apart from archaeol derived phytane caldarchaeol derived C 40 , isoprenoids with 0, 1 and 2 cyclopentane rings were found. This, as well as the potential existence of hydroxarchaeaol derived side chains, is in contrast to the ¢ndings of Hafenbradl et al [17] who found only archaeol derived phytane in the polar lipid fraction of MPK. The di¡erent protocols used for total lipid extraction might serve as an explanation for the observed discrepancies.…”
Section: Plel In Archaeacontrasting
confidence: 55%
“…The di¡erent protocols used for total lipid extraction might serve as an explanation for the observed discrepancies. Hafenbradl et al [17] as well as Morii et al [16] extracted lipids from MPK and MTF, respectively, with an acidi¢ed solvent according to Nishihara and Koga [18]. The two strains of Clostridia (CLA and CLB) showed a totally di¡erent PLEL pattern than the archaeal strains.…”
Section: Plel In Archaeamentioning
confidence: 99%
“…30) Digeranylgeranylglycerol (unsaturated archaeol) was first discovered by Hafenbradl et al 31,32) in the nonpolar lipid fraction of Methanopyrus kandleri. They reported in the same paper, 32) however, that the core lipid prepared by HCl-methanolysis of polar lipids of the organism was composed only of saturated archaeol. But Sprott et al 33) have shown the presence of unsaturated archaeol-based phospholipids, the most abundant of which is unsaturated archaetidylcholine, in the same archaeon by MS of total lipids.…”
Section: Allyl Ether Type Core Lipids From Methanopyrus Kandleri and mentioning
confidence: 99%
“…28) unsaturated archaetidylethanolamine, and archaetidylethanolamine, six archaeol-based glycolipids with one to six hexose units, and one tetraether type phosphoglycolipid, dihexosyl caldarchaetidylglycerol, have been identified, mainly by FAB-MS. 33) Total lipid of M. kandleri is rich in non-polar lipid (the polar lipid fraction represents only 50% of the total lipids), and more than 92% of the polar lipids are glycolipids. 32) Of the four kinds of glycolipid-sugar, mannose is predominant (86%). Such membrane lipid composition appears to be unique compared with that of other microorganisms.…”
Section: Allyl Ether Type Core Lipids From Methanopyrus Kandleri and mentioning
confidence: 99%
“…It is suggested, though not proven, that in such organisms the polar head groups contribute to membrane rigidity [114,115]. With the publication of lipid analyses of an increasingly diverse range of hyperthermophilic archaea, the diversity of lipids is rapidly increasing with, for example, the identification of fatty acids in the marine archaeon P. furiosus, unsaturated diether lipids in Methanopyrus kandleri [116], 36-membered macrocyclic diether lipids in Methanococcus jannaschii ( fig. 3g) [117] and tetraether lipids containing a covalent cross-link at the centre of the isoprenoid chains in Methanothermus fer6idus ( fig.…”
Section: Lipids Of the Thermophilic Archaeamentioning
confidence: 99%